MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA (SMP) INKLUSI TAMAN PENDIDIKAN DAN ASUHAN JEMEBR - Sholihah, Imro'atus; Ahmansuro, Luluk (LP2M STAI AL-UTSMANI BONDOWOSO, 2022)
This study aims to eliminate discrimination between children with special needs who can study together with normal children, so that it affects the growth and development of students.The focus of this research is